(untitled) (Journal of Economics and Sustainability, 2019)
With the introduction of entrepreneurial education in colleges, the quality evaluation of entrepreneurship education is the key to further develop entrepreneurship education. In China, different types of colleges have different training objectives. As such, classified management and guidance for different types of colleges and universities and a multi-level entrepreneurship education evaluation system are required. Based on the analysis of the current problems of entrepreneurship education in China, the education evaluation content can be divided into four categories: entrepreneurship curriculum, teacher team, students, and entrepreneurial environment. This paper puts forward the evaluation system in regular colleges and high vocational colleges to promote the development of entrepreneurship education.